POLITICAL PARTICIPATION OF NAGA WOMEN IN ELECTORAL POLITICS - Murry, Chibeni (International Journal of Research -GRANTHAALAYAH, 2024)
Patriarchy is deeply rooted in the Naga society and men are taught to live and believe for centuries that women are inferior to men. This societal conditioning of men has made them perceive themselves as leaders. Women were always sidelined and were considered politically lacking the ability to govern. Therefore they were not given the opportunity to take part in the decision making process. This article seeks to study the political representation of Naga women and how they were politically marginalized as a result of societal norms and attitudes. In the past the societal discriminatory mindset has forced women to prioritize gender role as care givers rather than take part in decision making. However gradual changes have started taking place as we see few women coming out to participate in decision making. But more women still need to come forward as adequate representation of women is an indicator of gender political equality in a true democracy. The study will attempt to highlight the role and contribution of Naga women in the past, present and future of Naga politics in Nagaland.